2019
DOI: 10.1038/s41598-019-40019-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional divergence of thyrotropin beta-subunit paralogs gives new insights into salmon smoltification metamorphosis

Abstract: Smoltification is a metamorphic event in salmon life history, which initiates downstream migration and pre-adapts juvenile salmon for seawater entry. While a number of reports concern thyroid hormones and smoltification, few and inconclusive studies have addressed the potential role of thyrotropin (TSH). TSH is composed of a α-subunit common to gonadotropins, and a β-subunit conferring hormone specificity. We report the presence and functional divergence of duplicated TSH β-subunit paralogs (tshβa and tshβb) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 71 publications
1
31
1
Order By: Relevance
“…Smolting is a hormonally controlled process and photoperiod-dependent changes in the secretion of anterior pituitary trophic hormones (ACTH, GH and TSH), together with cortisol and IGF-1, have been reported [2,15,19,50,51]. Importantly, the same hormones are not influenced by increased day length in salmon juveniles below a threshold body size for smolting [2,4,52,53].…”
Section: Discussionmentioning
confidence: 98%
“…Smolting is a hormonally controlled process and photoperiod-dependent changes in the secretion of anterior pituitary trophic hormones (ACTH, GH and TSH), together with cortisol and IGF-1, have been reported [2,15,19,50,51]. Importantly, the same hormones are not influenced by increased day length in salmon juveniles below a threshold body size for smolting [2,4,52,53].…”
Section: Discussionmentioning
confidence: 98%
“…In birds and mammals, PT-TSH acts retrogradely on hypothalamic area and is involved in the brain regulation of seasonal life-traits, such as reproduction, migration and hibernation [for reviews: ( 22 24 )]. A similar potential role in the seasonal regulation of smoltification could be hypothesized for the tshβb paralog in salmon ( 17 ). While in birds and mammals, both pituitary TSH cell populations express the same single tshβ gene, the two TSH cell populations in Atlantic salmon express distinct tshβa and tshβb paralogs.…”
Section: Introductionmentioning
confidence: 53%
“…Our recent studies in Atlantic salmon, Salmo salar , revealed a remarkable functional divergence of the duplicated tshβ paralogs, with a striking peak of pituitary tshβb transcripts at the time of smoltification, in early April, concomitantly with the change in rheotaxism and initiation of downstream migration, whereas no change was observed for tshβa . While previous studies by many authors in salmonids had only concerned the “classical” tshβa paralog, the demonstration of another paralog and its expression peak at smoltification provided the first evidence for the involvement of TSH in smoltification metamorphosis ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, genome duplication in fish may have allowed for some level of plasticity through specialisation of paralogues along the putative TSH/DIO/T3 axis. Fleming et al reported the expression of two distinct Tshß subunits in the salmon pituitary, one of which ( Tshßb) exhibits a marked induction as daylength increases from late winter onwards and a specific pattern of expression in the dorsal region near the pituitary stalk, a location comparable to the PT in mammals. Differential tissue expression and a response to photoperiod has also been reported for Dio2 paralogues in salmon .…”
Section: Challenges and Insightsmentioning
confidence: 99%